Changes in the Xingu River flooded vegetation caused by Belo Monte Dam: an approach using cointegration analysis and remote sensing images - Fernandez Molina, Kevin Anthony (2023)
The operation of Belo Monte hydroeletric plant has had significant on the natural hidrological cycle of the Xingu River. The hypothesis of this work suggests that the construction of the Belo Monte plant has caused a significant impact on the ecosystem, mainly through changes in hydrological dynamics, which in turn have induced alterations in the regions\'s floodplain vegetation. To test this hypothesis, the study aimed to determine the existence of a causal relationship between the time series data of the Normalized Difference Vegetation Index (NDVI) and the river water level (NCA), using the autoregressive model of Distributed Lags (ARDL). Where a structural causal relationship between these series was obtained as a result, which indicates a dynamic relationship between the NDVI and the NCA which can generate long-term effects such as variations in biodiversity, changes in forest structures and even alterations in the ecosystem around the Xingu river